2017
DOI: 10.1002/lary.26892
|View full text |Cite
|
Sign up to set email alerts
|

Survival of renal cell carcinoma metastatic to nonthyroid head and neck region: A systematic review

Abstract: Complete metastasectomy was associated with 4-year longer median overall survival than incomplete metastasectomy or no metastasectomy. Laryngoscope, 128:889-895, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lieder et al (93) demonstrated a rate of metastatic disease to the head and neck from RCC of 3.3% (22/671 patients) of all patients they treated with RCC, which they felt was sufficient enough to recommend for neck to be included in staging investigations for RCC. Liou et al (101) in a systematic review found a much higher rate of 14-16%, and so this advocates this recommendation even further. Crucially, metastases to the head and neck can result in severe morbidity and mortality involving airway obstruction, haemorrhage and airway obstruction, and for this reason both screening and treatment can be advocated.…”
Section: Table 3-key Literature Review Of Renal Carcinoma Oligometast...mentioning
confidence: 86%
“…Lieder et al (93) demonstrated a rate of metastatic disease to the head and neck from RCC of 3.3% (22/671 patients) of all patients they treated with RCC, which they felt was sufficient enough to recommend for neck to be included in staging investigations for RCC. Liou et al (101) in a systematic review found a much higher rate of 14-16%, and so this advocates this recommendation even further. Crucially, metastases to the head and neck can result in severe morbidity and mortality involving airway obstruction, haemorrhage and airway obstruction, and for this reason both screening and treatment can be advocated.…”
Section: Table 3-key Literature Review Of Renal Carcinoma Oligometast...mentioning
confidence: 86%
“…The median overall survival period was 36 months after diagnosis of metastasis, increasing to 60 months in those who underwent complete metastasectomy, which was significantly higher than in those who underwent incomplete metastasectomy or no metastasectomy. 30 In another study, half of patients with RCC metastasized to the oral cavity died within 1 year. 31…”
Section: Discussionmentioning
confidence: 99%
“…There is no common consensus on how to treat such patients.The treatment depends on characteristics of tumour and patient status.Such as performance status,patient's choice,risk factors,nature of metastasis [8].The treatment of such metastases include metastasectomy whenever possible and palliative chemotherapy,radiotherapy.Surgery is recommended as the first option of treatment if there is no other organ involvement.Tzyy et al showed in their metaanalysis that complete metastasectomy from head and neck region has superiority to incomplete metastasectomy and no metastasectomy.The median overall survival was significantly higher in complete metastasectomy patients [8].…”
Section: Case Reportmentioning
confidence: 99%